Construction of a monthly dynamic sediment delivery ratio model at the hillslope scale: a case study from a hilly loess region - Xu, Zan; Zhang, Shanghong; Hu, Xujian; Zhou, Yang (Frontiers in Environmental Science, 2024)
Soil loss is a worldwide environmental problem, and sediment transport is one of its important components. In recent years, a hillslope sediment delivery ratio (SDR) model based on an index of connectivity has been widely used to describe the variation in sediment transport characteristics. However, the hillslope SDR model only considers the structural characteristics of the watershed and ignores the dynamic mechanism of sediment transport, which leads to poor dynamic applicability over short timescales and makes it difficult to reflect changes of sediment yield. Therefore, we here propose a monthly dynamic SDR model that integrates the hillslope structural connectivity and sediment transport threshold of rainfall event based on the main influencing factors of sediment delivery. We then combine the dynamic SDR model with an empirical erosion model to simulate the hillslope sediment yield in the Mahuyu watershed, and verify the applicability of the coupled model using the Heimutouchuan watershed. The results show that the coupled model can effectively simulate the hillslope sediment yields of the Mahuyu and Heimutouchuan watersheds. The contribution of the rainfall transport threshold factor to sediment delivery and yield is essentially in dynamic stability at the multi-year timescale, but increases the heterogeneity of both inter-month distributions and the spatial distribution of hillslope sediment yield. The dynamic SDR model, which considers the rainfall thresholds of transport and re-transport, can effectively improve the simulation accuracy of low and high sediment yield values on hillslopes. Our results can provide a reference for understanding sediment transport processes on hillslopes and optimizing soil and water conservation measures in watersheds.